2011
DOI: 10.1128/aem.05544-11
|View full text |Cite
|
Sign up to set email alerts
|

High Yields of 2,3-Butanediol and Mannitol in Lactococcus lactis through Engineering of NAD + Cofactor Recycling

Abstract: Manipulation of NADH-dependent steps, and particularly disruption of the las-located lactate dehydrogenase (ldh) gene in Lactococcus lactis, is common to engineering strategies envisaging the accumulation of reduced end products other than lactate. Reverse transcription-PCR experiments revealed that three out of the four genes assigned to lactate dehydrogenase in the genome of L. lactis, i.e., the ldh, ldhB, and ldhX genes, were expressed in the parental strain MG1363. Given that genetic redundancy is often a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 62 publications
(79 reference statements)
0
40
1
Order By: Relevance
“…The maximum titers of (3 R )-acetoin, R-BDO and m-BDO obtained in this study were 27, 43 and 51 g/L respectively and the yield achieved was around 78 to 89% of theoretical maximum. The yield of 2,3-BDO achieved in this study for L. lactis was higher than obtained by Gaspar et al 22. (67% of theoretical maximum), where formate and ethanol were additional by-products.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The maximum titers of (3 R )-acetoin, R-BDO and m-BDO obtained in this study were 27, 43 and 51 g/L respectively and the yield achieved was around 78 to 89% of theoretical maximum. The yield of 2,3-BDO achieved in this study for L. lactis was higher than obtained by Gaspar et al 22. (67% of theoretical maximum), where formate and ethanol were additional by-products.…”
Section: Discussioncontrasting
confidence: 77%
“…It has previously been shown that when butA was over-expressed in an engineered L. lactis strain, m-BDO could be formed22. To completely eliminate m-BDO formation and achieve (3 R )-acetoin as the sole fermentation product, we therefore further inactivated the native butB and butA genes, which are co-located in an operon, thus generating VJ017 (MG1363 Δ 3 ldh Δ pta Δ adhE Δ butBA ) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Exceptions are e.g. the seven rrn operons in E. coli (Stevenson & Schmidt, 2004), the four lactate dehydrogenases in Lactococcus lactis (Gaspar et al, 2011), and the three tcpD detoxification genes for the degradation of haloaromatic compounds in Cupriavidus necator (Pérez-Pantoja et al, 2009). In most cases there is a clear physiological function for this redundancy: high transcript levels that cannot be provided with a single promoter (in E. coli and Lactococcus), and differentiated selectivity of the separate promoters, or the advantage of rapid response in environments defined by fluctuations in resource availability, in the case of Cupriavidus.…”
Section: The Mechanism Of Light Inhibition Of Twitching Motilitymentioning
confidence: 99%
“…Many studies have detailed the ADH gene and its activity for Lactococcus lactis ssp. lactis in the field of sugar and ethanol production (Even et al, 2001;Palmfeldt et al, 2004;Gaspar et al, 2011;Solem et al, 2013;Costa et al, 2014;Gänzle, 2015).…”
Section: Introductionmentioning
confidence: 99%